Tests of a novel sensor for α-spectrometry in drinking water matrices. (September 2015) - Diener, A.; Wilhelm, C.
Abstract: The technical innovation of boron-doped diamond on top of a silicon layer as alpha nuclide measurement device offers promising advances, since the energy-resolved measurement takes place in-situ in water without matrix separation. Several experiments were performed to detect disturbance factors by investigating the yield of 241 Am in the presence of main or minor drinking water elements. The results show that an activity was detected by the sensor in any case. Generally, the yields were higher with NaNO3 as electrolyte than with Na2 SO4, due to speciation and higher hydrogen formation. A reduced yield was observed for nitrate as electrolyte and maximum concentrations of Ca, Mg, PO4, and F in drinking water. The generally high standard deviation of the measurement, which is mainly due to hydrogen evolution, mass attenuation, and surface site occupation, does not allow for an exact determination of a present α-contamination. However, a significant aqueous alpha activity can be detected. Highlights: Sensor allows energy-resolved measurements of alpha nuclides w/o separation. B-NCD/Si-device detected a significant activity in any case. Surface site occupation and hydrogen evolution lead to high standard deviations.